Images of occupation in Dutch film : memory, myth, and the cultural legacy of war - Burke, Wendy (Framing film (Amsterdam, Netherlands), 2017)
'Images of Occupation in Dutch Film' is the first book in English to examine changing representations of the German wartime occupation of the Netherlands within Dutch post-war feature films made in the period 1962 to 1986. This important new study explores in detail the complex, evolving role played by film within Dutch cultural memory and asks to what extent film can fully embrace, transmit or assimilate the complexities and collective legacies of war and occupation. As Dutch public opinion toward the war altered over the post-war decades - attitudes to the 1940-1945 occupation, Jewish persecution, the enemy, deprivations, resistance and collaboration - so too shifted the presence - or indeed absence - of these elements in subsequent films. The historical trajectory of Dutch recovery and reconstruction: politically, economically and - most complex of all - psychologically, came to be revealed, often unconsciously, in the films from that time. Through detailed analyses of eight key film texts ranging from 1962's De Overval, to Verhoeven's Soldaat van Oranje and Rademakers' De Aanslag, this book offers valuable insights into the previously under-explored connections between filmic images of occupation and how these reflect parallel shifts in Dutch society's perceptions about the war at the times the films were made. It asks how a nation's films re-tell its history.